Opuntia spp.: An Overview of the Bioactive Profile and Food Applications of This Versatile Crop Adapted to Arid Lands - Carolina Rodrigues; Camila Damásio de Paula; Soufiane Lahbouki; Abdelilah Meddich; Abdelkader Outzourhit; Mohamed Rashad; Luigi Pari; Isabel Coelhoso; Ana Luísa Fernando; Victor G. L. Souza (Foods, 2023)
Opuntia spp. are crops well adapted to adverse environments and have great economic potential. Their constituents, including fruits, cladodes, and flowers, have a high nutritional value and are rich in value-added compounds. Cladodes have an appreciable content in dietary fiber, as well as bioactive compounds such as kaempferol, quercetin, and isorhamnetin. Fruits are a major source of bioactive compounds such as phenolic acids and vitamin C. The seeds are mainly composed of unsaturated fatty acids and vitamin E. The flowers are also rich in phenolic compounds. Therefore, in addition to their traditional uses, the different plant fractions can be processed to meet multiple applications in the food industry. Several bakery products have been developed with the incorporation of cladode flour. Pectin and mucilage obtained from cladodes can act as edible films and coatings. Fruits, fruit extracts, and fruit by-products have been mixed into food products, increasing their antioxidant capacity and extending their shelf life. Betalains, obtained from fruits, can be used as food colorants and demonstrate promising applications as a sensor in food packaging. This work reviews the most valuable components of the different fractions of this plant and emphasizes its most recent food applications, demonstrating its outstanding value.